Selling in a crisis : 55 ways to stay motivated and increase sales in volatile times - Blount, Jeb (Ascent Audio, 2022)
In Selling in a Crisis, the world's most sought-after sales trainer Jeb Blount delivers an essential blueprint for staying motivated, keeping your pipeline full, increasing sales, retaining your customers, and advancing your career in times of uncertainty and change. In his classic, no-nonsense style, Jeb gives you fifty-five easy to consume tips, techniques, and tactics that are time-tested and proven to help you stay on top when everything and everyone else is down. You'll also discover: the real secrets to selling more in a crisis; how to be a right now sales professional; 7 Steps of Effective Prospecting Sequences and how to be professionally persistent; how to adjust sales messaging to meet the moment; The five questions you must answer in the affirmative for every stakeholder; five ways to protect and advance your career; and so much more ... Jon Kabat-Zinn once said, "You can't stop the waves, but you can learn to surf." This is exactly what you'll learn to do in this indispensable guide for sales professionals who are navigating the rough seas of volatility. With each chapter you will find the motivation, inspiration, and confidence catch to rise above the negativity, catch your wave, and take control of your life, career, mindset, and income